КРИЛАТІ ВИСЛОВИ ЯК ХУДОЖНЬО-ОБРАЗНИЙ ЗАСІБ СУЧАСНОЇ УКРАЇНСЬКОЇ ЛІТЕРАТУРНОЇ МОВИ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of the idiomatic functioning in the nominative system of the modern Ukrainian literary language.